CONCEPTS OF SCHOOL: APPROACHES TO THE CHILEAN EDUCATION SYSTEM FROM CONCEPTUAL HISTORY. 1840-1890. - Mayorga, Rodrigo (Revista de Historia Social y de las Mentalidades, 2011)
During the ninetieth century, one of the most important concerning of the Chilean State was to establish a public educational system that would extend education throughout the territory. However, the novelty of this institution led the institutional actors to the need of conceptualize and define the school itself, the effects expected to be attained with this and the means to achieve it. This article aims to investigate this process from an approach of conceptual history. From the postulates presented by the historian Reinhart Koselleck, we investigate how the institutional actors conceptualized the role of the school, both in terms of its modifier capacity and the effects that they was looking to get through it. During the period between the 1840s and 1880s, schools were understood as institutions capable of transforming individuals who assisted to them, which led to the priority need of establish uniformity by surveillance and control. At the same time, the apparent consensus about the civilizing role of the school was given with a constant tension between moralizing and modernizing elements embedded in it, which led to raise emphasis and nuances within the objectives pursued by the school, but always circumscribed within the general framework of the transformation of individuals to benefit the nation-state project proposed by the ruling classes